Global and communicative development skills in preschool children with cleft lip and palate - Mayalle Rocha Bonfim Jurado; Maria Gabriela Cavalheiro; Camila deCastro Corrêa; Melina Evangelista Whitaker; Simone Rocha deVasconcelos Hage; Dionísia Aparecida Cusin Lamônica; Luciana Paula Maximino (Wiley, 2021)
ABSTRACT Importance Cleft lip and palate (CLP) is globally among the most common childhood malformations. This disorder impacts childhood development, including speech and language, and affects children worldwide. Objective To analyze child development skills (adaptive fine motor, gross motor, personal‐social, and language) in preschool children with isolated CLP compared with children without this malformation. Methods The participants included an experimental group of 27 children with isolated CLP and a comparison group of 27 children without CLP aged between 48 and 59 months. The groups were evaluated using two instruments: the Denver Developmental Screening Test II (DDST‐II) and the Avaliação do Desenvolvimento da Linguagem (ADL‐Language Development Assessment). Data were analyzed by descriptive and inductive analyses, using the Student's t‐test and the Mann‐Whitney test, at a significance level of P ˂ 0.05. Results All children in the comparison group performed within normal standards for their age range in the DDST‐II and the ADL. The worst performance in the experimental group was observed in language skills, followed, in declining order, by adaptive fine motor, personal‐social, and gross motor as measured by the DDST‐II. Children with isolated CLP also performed poorly in receptive, expressive, and global language in the ADL. No statistically significant differences were observed in the experimental group's scores for the ADL and the DDST‐II. Interpretation Developmental skill levels were below expectations for children of this age with isolated CLP.